Resectable Pancreatic Cancer: Is Surgery the Best First Step? - Russo, Suzanne; Chabot, John; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
<p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; background-image: initial; background-attachment: initial; background-origin: initial; background-clip: initial; background-color: white; background-position: initial initial; background-repeat: initial initial;">Controversy exist regarding the potential benefit of the neoadjuvant approach to pancreatic cancer as limited retrospective data exists comparing pre- with post-operative chemoradiation. The optimal treatment approach remains unclear as we await prospective randomized clinical trials evaluating the hypothesized benefit of the neoadjuvant therapy for resectable pancreatic cancer and as there has been no proven survival benefit to date. Here we summarize the data presented at the 2012 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium providing additional insight into the potential of neoadjuvant therapy in the treatment of pancreatic cancer. (Abstracts #156, #162, #168 and #177).